ECRANISATION OF INTRINSIC ELEMENTS IN THE NOVEL AND FILM CINTA DALAM IKHLAS - Muhammad Danial; Rezky Khoirina Tarihoran; Ayu Melati Ningsih; Diana Sopha (Universitas Gunadarma, 2026)
This study aims to describe the ecranisation process of intrinsic elements, including plot, characters, and settings, from the novel